La transacción en el proceso laboral y la renuncia de los derechos del trabajador. - MOROCHO GRANDA, TONI ROMEL (2013)
The labor transaction considered as a contract in which the parts even arrive agreement, product for which the Litis ends, where the worker gives up their rights settled down in the law, like they are; vacations, tenth third and quarter salary, a remuneration or basic salary, the payment of the extra hours, etc. This silk most from necessity of the worker, where it has lost time and money and the other part like he/she is the employer the reaching an agreement it is simply saved time and money. Some authors criticize the transaction contract alleging that the same one constitutes an immorality, since the men without scruples take advantage of the fear that one generally has to the judicial processes to achieve, advantageous transactions. To try to maintain the social peace they say the justice it is sacrificed. It is also sustained that the economically more powerful part imposes to the weakest, to which lacks enough resources to finance the expenses that it demands a long process, the conditions of the transaction. At the same informed time of the problems that causes the labor transaction and the renouncement of the worker's rights, it is necessary to write down different legal bodies with the purpose of precautelar the such worker's rights as: the Constitution of the Republic, The Code of the Work norms that you/they aid directly to the worker's rights, likewise Institutions Publish in charge of to take care and to make respect rights that he/she has the workers, which are: The Ministry of Labor Relationships, The inspectoría of the Work and the Tribunals of the Labor thing whose purpose is the protection and direct help of the worker's rights From my point of view I believe that the authorities don't fulfill to cabalidad the functions commended in to take care and to protect the worker's rights, for what in the labor transaction the principle of Irrenunciabilidad of the worker's rights is not respected whose principle is universal and protective of the worker's interests.